EVALUASI PROGRAM PEMBELAJARAN TEMATIK DI SEKOLAH DASAR KELAS BAWAH SDN 1 CIUYAH - Arini, Ira (Jurusan Pendidikan Guru Madrasah Ibtidaiyah Fakultas Tarbiyah dan Keguruan Universitas Islam Negeri Sultan Maulana Hasanuddin Banten, 2022)
Based on the 2006 Minister of National Education Regulation concerning content standards for SD/MI level education units which cover the substance of grades 1 to III which are implemented through thematic learning, there has been no comprehensive program evaluation in the implementation of low-grade thematic learning. Therefore, the purpose of this study was to assess the thematic learning program implemented in lower grade elementary schools. The research method used is a program evaluation research method with data collection techniques in the form of interviews, document analysis, questionnaires and observations. The results showed that the thematic learning program was divided into 3 stages, namely planning, implementation and evaluation. At the learning planning stage, the score obtained from the results of document analysis and observations of 3 evaluators was 3.2 with a good category and supported by the results of questionnaires and teacher interviews which stated that the teacher had prepared the stages of planning thematic learning in accordance with the basic concepts of thematic learning. At the implementation stage of learning, the score obtained was 3.5 with a very good category and supported by the results of questionnaires and teacher interviews which stated that the process of implementing learning in lower grade elementary schools was carried out thematically. At the learning evaluation stage, the score obtained was 2.7 with a good category and supported by the results of questionnaires and teacher interviews which stated that the thematic learning evaluation had been applied.